The effect of Adobe Premiere Pro application based on Project Based Learning to critical thinking skills of class XI students of the Visual Communication Design majoring at SMK Negeri 1 Kota Serang - Pandu Dewantara; Basrowi; Kurniati Rahmadani (Cakrawala Pedagogik, 2023)
One of the ideal demands of the 2013 curriculum is the use of technology as a learning application to improve students critical thinking skills. And one of them is the Adobe Premiere Pro application based on Project Based Learning to students critical thinking skills at SMK Negeri 1 Kota Serang. This study aims to determine the effect of the Adobe Premiere Pro application based on Project Based Learning to critical thinking skills of class XI students of the Visual Communication Design Majoring at SMK Negeri 1 Kota Serang. This study uses a quantitative research method, namely as a research method used to examine certain samples, documentation, and data instruments in the form of questionnaires. This research includes the type of experimental research, namely to process research in more detail about a problem, research that explains what is happening in the field in the form of numbers and is supported by quantitative data. The sampling technique in this study was random sampling. The population in this study were 78 students with a total sample of 40 students. Data collection techniques in this study were questionnaires, observation sheets and documentation. The results of this study can be concluded that the Adobe Premiere Pro application variable based on Project Based Learning contributes 52.4% to changes in students' critical thinking ability variables. Based on the results of the t test, the average value was ????calculate>????????????????le (6.469 > 1.686), and the significance value was 0.05 (5%), thus ???????? was rejected and ????1 was accepted. This proves that there is an influence of the Adobe Premiere Pro application based on Project Based Learning on the critical thinking skills of class XI students majoring in Visual Communication Design at SMK Negeri 1 Kota Serang.